Application of glucocorticoids in patients with novel coronavirus infection: From bench to bedside - Linwei Lu; Jianhua Huang; Xiaohong Deng; Xianjun Sun; Jingcheng Dong (World Scientific Publishing, 2020)
Glucocorticoids (GCs) have potential anti-inflammatory and immunosuppressive effects. There is plenty of controversy about the application of glucocorticoids in the treatment of coronavirus disease 2019 (COVID-19). This paper briefly summarizes the mechanism of glucocorticoids and their receptors and clinical applications in COVID-19. Through reviewing the current literature, our aim is to have a deeper understanding of the mechanism of GCs and their clinical applications, so as to find possible ways to enhance their efficacy and reduce drug resistance or side effects.